Long-Term Clinical and Angiographic Outcomes Following Pipeline Embolization Device Treatment of Complex Internal Carotid Artery Aneurysms: Five-Year Results of the Pipeline for Uncoilable or Failed Aneurysms Trial - Becske, Tibor; Brinjikji, Waleed; Potts, Matthew B.; Kallmes, David F.; Shapiro, Maksim; Moran, Christopher J.; Levy, Elad I.; McDougall, Cameron G.; Szikora, István; Lanzino, Giuseppe; Woo, Henry H.; Lopes, Demetrius K.; et al. (Neurosurgery, 2017)
Abstract BACKGROUND: Early and mid-term safety and efficacy of aneurysm treatment with the Pipeline Embolization Device (PED) has been well demonstrated in prior studies. OBJECTIVE: To present 5-yr follow-up for patients treated in the Pipeline for Uncoilable or Failed Aneurysms clinical trial. METHODS: In our prospective, multicenter trial, 109 complex internal carotid artery (ICA) aneurysms in 107 subjects were treated with the PED. Patients were followed per a standardized protocol at 180 d and 1, 3, and 5 yr. Aneurysm occlusion, in-stent stenosis, modified Rankin Scale scores, and complications were recorded. RESULTS: The primary endpoint of complete aneurysm occlusion at 180 d (73.6%) was previously reported. Aneurysm occlusion for those patients with angiographic follow-up progressively increased over time to 86.8% (79/91), 93.4% (71/76), and 95.2% (60/63) at 1, 3, and 5 yr, respectively. Six aneurysms (5.7%) were retreated. New serious device-related events at 1, 3, and 5 yr were noted in 1% (1/96), 3.5% (3/85), and 0% (0/81) of subjects. There were 4 (3.7%) reported deaths in our trial. Seventy-eight (96.3%) of 81 patients with 5-yr clinical follow-up had modified Rankin Scale scores ≤2. No delayed neurological deaths or hemorrhagic or ischemic cerebrovascular events were reported beyond 6 mo. No recanalization of a previously occluded aneurysm was observed. CONCLUSION: Our 5-yr findings demonstrate that PED is a safe and effective treatment for large and giant wide-necked aneurysms of the intracranial ICA, with high rates of complete occlusion and low rates of delayed adverse events.